Analisis Kerusakan Jalan Flexible Pavement dengan Metode Pavement Condition Index (PCI) pada Jl. Kates – Jl. Gedangrowo Kecamatan Prambon Kabupaten Sidoarjo - Fikri, Dzaki Arif; Hartatik, Nurani; Firmansyah, Mochamad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Kates – Gedangrowo Highway located in Prambon District, Sidoarjo Regency is a local road type 2/2 UD with a length of 3.4 km and a width of 8 meters. This road experiences various types of damage such as crocodile cracks, potholes, patches, obesity, sinkholes, cracks on the edge, grain detachment, and longitudinal cracks. The purpose of this study is to identify the type of damage by analyzing the condition of the pavement using the PCI. From the results of the field survey on 34 segments, 10 types of damage were detected with the results of the study showing that there were 255 points of damage with the dominant type of Alligator Cracking of 27.06%, Potholes of 27.06%, and Patching of 20.78%. The average PCI value of the entire road section is 49.8 which is included in the Fair category. However, 12 segments (1,200 meters) were found to be in Failed and Very Poor condition, requiring immediate priority treatment. Treatment recommendations vary, including total reconstruction, rehabilitation with overlays, periodic maintenance, and routine maintenance tailored to the conditions of each segment, using the method as the basis for calculating the Cost Budget Plan.